Goat Science - Environment, Health and Economy 2023
DOI: 10.5772/intechopen.97792
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Goat Production in Southern Africa: A Review

Abstract: Goats play a crucial role in improved livelihoods and food security in Africa. Indigenous and locally developed types exhibit a wide range of phenotypic diversity, but are commonly well adapted to the harsh environment in which they need to survive and produce. They have various functions in communities in developing countries, from providing food security to being a liquid form of cash and playing a role in ceremonial occasions. The Southern African goat population exceeds 35 million animals, most of which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Goats play a particularly important role in domestic affairs in much of Africa. There are approximately 425 million goats in Africa, with roughly 5.2 million of these in South Africa (Mataveia et al, 2021 ). In South Africa, there are both a commercialized, intensive goat production system, and a semi‐intensive system that consists of small farming cooperatives and individual farmers (Mdladla et al, 2017 ; Morrison, 2007 ).…”
Section: Study Organism and Community Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Goats play a particularly important role in domestic affairs in much of Africa. There are approximately 425 million goats in Africa, with roughly 5.2 million of these in South Africa (Mataveia et al, 2021 ). In South Africa, there are both a commercialized, intensive goat production system, and a semi‐intensive system that consists of small farming cooperatives and individual farmers (Mdladla et al, 2017 ; Morrison, 2007 ).…”
Section: Study Organism and Community Contextmentioning
confidence: 99%
“…The Nguni goats used in this study are part of this semi‐intensive “village” goat system, which is characterized by animals with limited housing and veterinary care that are generally adapted to harsh conditions. This production system usually consists of informal labor, with herders overseeing small herds with minimal use of technology and other inputs (Mataveia et al, 2021 ). Production performance and goat behavior in these village goat systems are much less studied than in commercialized systems (Masika & Mafu, 2004 ; Ncube et al, 2020 ), but research on these systems could help contribute to management practices that provide benefits to marginalized communities.…”
Section: Study Organism and Community Contextmentioning
confidence: 99%
“…Studies have indicated that goats respond better to environmental heat stress than other livestock animals [ 48 , 49 ]. They can cope better, even when farmed with other livestock species [ 1 ]. Due to various morphological, phenotypic, and largely genetic traits, they can adapt to any environmental condition [ 50 ].…”
Section: Adaptation Of Indigenous Goat To Local Environmentsmentioning
confidence: 99%
“…The African goat population accounts for at least 41% of the world’s goat population, which equates to approximately 423 million goats, of which, 35 million come from Southern Africa [ 1 , 2 ]. South Africa is the third-highest goat-producing country in Southern Africa, preceded by Tanzania and Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to increase the number of goats and increase their productivity. 4 Improving goat production has been an on-going challenge at both academic, institutional, village, and individual farmer levels, and a major pathway is through breeding. Benefits from genetic improvement that add value to goat meat endproducts could achieve sustainable development and reach a wider population of the poor and needy.…”
mentioning
confidence: 99%